Children, Media and Playground Cultures - Willett, R. author. aut Link
XI, 268 p.
Keywords: Drawing on ethnographic accounts of children's media-referenced play, this book explores children's engagement with media cultures and playground experiences, analyzing a range of issues such as learning, fantasy, communication and identity.